Distribution of three Euphorbiaceae species, Endospermum diadenum (Sesendok), Macarangan gigantae (Mahang Gajah) and Macaranga hypoleuca (Mahang Kapur) in UiTM Jengka forest reserve - Mohamad Isa, Mohamad Faizul Azam; Zamri, Muhammad Amir; Rusman, Mohd Khalid (2010)
The UiTMJFR is a forest reserve in Pahang with about 250 acres. This study was conducted to record the distribution of Euphorbiaceae species such as Macaranga gigantae (Mahang gajah) and Endospermum diadenum (Sesendok), Macaranga hypoleuca (Mahang kapur) in UiTM Jengka Forest Reserve at line 1,2,3,4,5,11,12, 13,14, and 15. UiTMJFR has abundance of Euphorbiaceae species, but we decided to choose three from them because of timing constraint. In this study it was found 70%, 16%, and 14% for Sesendok, Mahang kapur and Mahang gajah respectively. Sesendok is most found in UiTM Jengka because it easily growth in lowland and expose to sunshine. This survey also to study a suitable height and diameter of trees growth in the forest.